Tissue-Type Plasminogen Activator and Tenecteplase-Mediated Increase in Blood Brain Barrier Permeability Involves Cell Intrinsic Complement - Keragala, Charithani B.; Woodruff, Trent M.; Liu, Zikou; Niego, Be'eri; Ho, Heidi; McQuilten, Zoe; Medcalf, Robert L. (Frontiers in Neurology, 2020)
Background: Tissue-type plasminogen activator (t-PA) has been the mainstay of therapeutic thrombolysis for patients with acute ischaemic stroke (AIS). However, t-PA can cause devastating intracerebral haemorrhage. t-PA can also influence the CNS in part by modulation of BBB permeability. Complement activation also occurs after AIS and has also been reported to increase BBB permeability. The complement components, C3 and C5, can also be activated by t-PA via plasmin formation and cell intrinsic complement may be involved in this process. Tenecteplase (TNK-tPA) is a t-PA variant with a longer plasma half-life, yet the ability of TNK-tPA to modulate the BBB and complement is less clear. Aim: To evaluate the effect of C5 and C5a-receptor 1 (C5aR1) inhibitors on t-PA- and TNK-tPA-mediated opening of the BBB. Methods: We used an in vitro model of the BBB where human brain endothelial cells and human astrocytes were co-cultured on the opposite sides of a porous membrane assembled in transwell inserts. The luminal (endothelial) compartment was stimulated with t-PA or TNK-tPA together with plasminogen, in the presence of PMX205 (a non-competitive C5aR1 antagonist), Avacopan (a competitive C5aR1 antagonist) or Eculizumab (a humanised monoclonal inhibitor of human C5). BBB permeability was assessed 5hr and 24hr later. Immunofluorescence was also used to detect changes in C5 and C5aR1 expression in endothelial cells and astrocytes. Results: PMX205, but not Avacopan or Eculizumab, blocked t-PA-mediated increase in BBB permeability at both the 5 and 24hr time points. PMX205 also blocked TNK-tPA-mediated increase in BBB permeability. Immunofluorescence analysis revealed intracellular staining of C5 in both cell types. C5aR1 expression was also detected on the cell surfaces and also located intracellularly in both cell types. Conclusion: t-PA and TNK-tPA-mediated increase in BBB permeability involves C5aR1 receptor activation from cell-derived C5a. Selective inhibitors of C5aR1 may have therapeutic potential in AIS.